Changing parental leave and shifts in second and third-birth rates in Austria - Anna Št'astná; Tomáš Sobotka (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2009)
We analyse the effects of changes in parental leave regulations in Austria in 1990, 1996 and 2002 on second and third-birth rates. These changes determined both the length of parental leave and the possibility for its prolongation in case of subsequent pregnancy. We construct monthly duration and order-specific fertility rates and parity progression ratios to study both short-term shifts in period second and third-birth rates and the trends in cohort parity progression ratios among women affected by changing leave regulations. The extension of parental leave from one to two years in 1990, which created an incentive for women to have their subsequent child within 26 months, led to an immediate and marked increase in second and third-birth rates at intervals 21-26 months after the previous birth. De facto shortening of paid leave in 1996 generated a sharp increase in second and thirdbirth rates at shorter intervals of 15-20 months. Although we find clear evidence of immediate changes in birth spacing that are in line with the 'logic' of the new leave regulations, this discontinuity in childbearing patterns did not have any discernable impact on the overall second and third-birth cohort progression rates or on period fertility trends. As in most cases analysed for other developed countries, the main effect of the policy change was on the tempo of fertility, namely on the spacing of second and third births.
Keywords: 300; Austria; parental leave; family policies; fertility; second births; third births; Elternzeit; Fertilität; Familienplanung; Privater Haushalt; Österreich